Changes in the indicators of the physical condition of students under the influence of classes in sports sections - Сухенко, Ігор (Slobozhanskyi Herald of Science and Sport, 2019)
Ihor Sukhenko Purpose: investigate changes in the indicators of the physical condition of students under the influence of classes in sports sections. Material & Methods: to solve the purpose, the following research methods were used: analysis and synthesis of references, methods for determining the functional state of the body, methods for assessing the level of physical health (using the methodology of G. L. Apanasenko), methods for determining motor activity, methods of mathematical statistics. The study involved 50 students of Volodymyr Dahl East Ukrainian National University Severodonetsk. Results: it was found that under the influence of classes in the sports sections of martial arts, the greatest improvement in physical condition indicators was observed. In the experimental groups (in martial arts and athletics) a greater positive trend was recorded than in the control group. An analysis of the practice of martial arts for indicators of the physical condition of students allows us to state that a marked optimization of the work of the cardiovascular and respiratory systems was noted. The positive effect of sectional athletics on physical condition indicators, especially on speed, was recorded. The study confirmed the feasibility of using sectional classes in martial arts and athletics with students. Conclusions: experimental materials presented in this study allowed us to state the pronounced positive effect of classes in athletics and martial arts sports sections on physical condition indicators, namely, on the functional state, level of physical performance and physical health of boys and girls aged 17–18. The most pronounced differences are observed in the indices of Rufe, Stange, Genchi, who significantly (p<0.01 (EG-1), p<0.001 (EG-2)) improved in both experimental groups.